Whole genome-sequence analysis of Bacillus subtilis strain KC14-1 with broad-spectrum antifungal activity - Xiaowei Li; Yahan Chen; Shunyi Yang; Yi Zhou; Chengde Yang (BMC Genomics)
Abstract Background Bacillus is used as a biological control agent in agricultural production. The main mechanisms responsible for its biocontrol activity encompass the generation of various antifungal active substances during life activities, competition, antagonism with pathogens, promotion of growth, and induction of plant resistance, enhancing the inhibition of pathogenic fungi. Bacillus has high biological control potential and has become a research hotspot. Results It was found that strain KC14-1 had significant inhibitory effects on Fusarium fujikuroi, Rhizoclonia solani, Alternaria solani, Fusarium oxysporum, and Valsa mali. Based on morphological observations, physiological and biochemical determinations, and 16 S rRNA, gyrA, and gyrB gene sequencing, strain KC14-1 was identified as Bacillus subtilis. Whole genome sequencing results showed that the genome of strain KC14-1 was composed of a ring chromosome 3,908,079 bp in size, with a GC content of 43.82% and 3,895 coding genes. Anti-SMASH predicted that the genome of strain KC14-1 contained nine gene clusters that synthesised antibacterial substances. The homology between fengycin, bacillibactin, pulcherriminic acid, subtilosin A, and bacilysin was 100%. Conclusion The biocontrol potential of Bacillus subtilis KC14-1 was determined through whole-genome analysis. Our study provides a solid foundation for developing and utilising this strain.